A boom‐or‐bust approach—The 'Glass Cannon' hypothesis in host microbiomes. Issue 5 (7th May 2021) - Antwis, Rachael
Abstract: In Focus: Dunphy, CM, Vollmer, SV, Gouhier, TC. (2021) Host–microbial systems as glass cannons: Explaining microbiome stability in corals exposed to extrinsic perturbations. Journal of Animal Ecology, 90, 1044–1057. The importance of symbiotic microbial communities for the functioning of animal hosts is now well‐documented; however, the interactions between host microbiomes and stress are less well‐understood. Dunphy et al. used a common garden experiment to show that host–microbiomes vary in their resilience across different coral species. The authors then used mathematical modelling to provide novel evidence that species with microbiomes that are regulated by host processes are robust to perturbation from stressors, but that robustness comes at a higher cost to the host. Conversely, species with microbiomes that are regulated by microbial processes are generally much more resilient and cheaper to support, but when disrupted by external stressors, the communities break down entirely—these latter species are termed 'glass cannons'. This novel hypothesis has important implications for how host microbiomes function in a rapidly changing world that exposes animal hosts to multiple biotic and abiotic perturbations. Abstract : This In Focus artilce is a summary of the 'Glass Cannon' hypothesis proposed by Dunphy et al. (2021). ​